2017
DOI: 10.1016/j.bbadis.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Translational effects and coding potential of an upstream open reading frame associated with DOPA Responsive Dystonia

Abstract: Upstream open reading frames (uORFs) have emerged as major post-transcriptional regulatory elements in eukaryotic species. In general, uORFs are initiated by a translation start codon within the 5' untranslated region of a gene (upstream ATG; uATG), and they are negatively correlated with translational efficiency. In addition to their translational regulatory role, some uORFs can code for biologically active short peptides. The importance of uATGs/uORFs is further underscored by human diseases associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…Even if the flanking sequence of the new ATG does not completely match the consensus predicted Kozak sequence ((G/A)NNAUGG), it seems similar to the one flanking the natural PROS1 ATG, suggesting that the new ATG could be identified by the translational machinery and thus used in the cells [30,31]. Several works have previously demonstrated that uAUG and uORF are cis-regulatory elements in 5 UTR that are able to control protein expression by altering the translation efficiency and could subsequently be associated with risk of diseases [32][33][34][35]. Many previously ignored uORFs are now known to act as major post-transcriptional regulatory elements or to be translated to produce bioactive peptides or proteins [36,37].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Even if the flanking sequence of the new ATG does not completely match the consensus predicted Kozak sequence ((G/A)NNAUGG), it seems similar to the one flanking the natural PROS1 ATG, suggesting that the new ATG could be identified by the translational machinery and thus used in the cells [30,31]. Several works have previously demonstrated that uAUG and uORF are cis-regulatory elements in 5 UTR that are able to control protein expression by altering the translation efficiency and could subsequently be associated with risk of diseases [32][33][34][35]. Many previously ignored uORFs are now known to act as major post-transcriptional regulatory elements or to be translated to produce bioactive peptides or proteins [36,37].…”
Section: Discussionmentioning
confidence: 97%
“…Several works have previously demonstrated that uAUG and uORF are cis-regulatory elements in 5 UTR that are able to control protein expression by altering the translation efficiency and could subsequently be associated with risk of diseases [32][33][34][35]. Many previously ignored uORFs are now known to act as major post-transcriptional regulatory elements or to be translated to produce bioactive peptides or proteins [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Several works have previously demonstrated that uAUG and uORF are cis-regulatory elements in 5‘UTR that are able to control protein expression by altering the translation efficiency and could subsequently be associated with risk of diseases (Dvir et al ., 2013; Lin et al ., 2019; Orr et al ., 2019; von Bohlen et al ., 2017). Many previously ignored uORFs are now known to act as major post-transcriptional regulatory elements or to be translated to produce bioactive peptides or proteins (Jones et al , 2017; Orr et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several examples of deregulated uORFs associated with the onset or development of rare diseases were well reviewed by Barbosa and co-workers 1 . Meanwhile, other cases have been described (Table 1), highlighting and reinforcing the impact of uORFs in mediating translational regulation in human health and disease [56][57][58][59][60][61] .…”
Section: Uorfs and Human Rare Diseasesmentioning
confidence: 96%
“…Other examples of rare diseases that can be related to the creation of uORFs include familial DOPA responsive dystonia (DRD) and acampomelic campomelic dysplasia (ACD) 56,59 . In the first case the polymorphism c.-22C>T in the 5'UTR of the human guanosine triphosphate cyclohydrolase 1 (GCH1) gene creates an out-of-frame uORF that encodes a 73-amino acid peptide, impairing the main ORF translation 56,57 . The subsequent low expression of GCH1 impairs the dopamine biosynthesis pathway that, ultimately, results in reduced levels of dopamine and dopaminergic dysfunction in the brain, typical of DRD.…”
Section: Rare Disease Gene Pathogenesis Referencementioning
confidence: 99%